Country data on AMR in Russia in the context of community-acquired respiratory tract infections: links between antibiotic susceptibility, local and international antibiotic prescribing guidelines, access to medicine and clinical outcome. (6th September 2022) - Torumkuney, Didem; Kozlov, Roman; Sidorenko, Sergey; Kamble, Praveen; Lezhnina, Margarita; Galushkin, Aleksandr; Kundu, Subhashri
Abstract: Background: Antimicrobial reistance (AMR) is one of the biggest threats to global public health. Selection of resistant bacteria is driven by inappropriate use of antibiotics, amongst other factors. COVID-19 may have exacerbated AMR due to unnecessary antibiotic prescribing. Country-level knowledge is needed to understand options for action. Objectives: To review AMR in Russia and any initiatives addressing it. Identifying any areas where more information is required will provide a call to action to minimize any further rise in AMR within Russia and to improve patient outcomes. Methods: National AMR initiatives, antibiotic use and prescribing, and availability of susceptibility data, in particular for the key community-acquired respiratory tract infection (CA-RTI) pathogens Streptococcus pneumoniae and Haemophilus influenzae, were identified. National and international antibiotic prescribing guidelines commonly used locally for specific CA-RTIs (community-acquired pneumonia, acute otitis media and acute bacterial rhinosinusitis) were also reviewed, plus local antibiotic availability. Insights from both a local clinician and a local clinical microbiologist were sought to contextualize this information. Conclusions: Russia launched a national strategy in 2017 to prevent the spread of AMR and the WHO reports that as of 2020–21, it is being implemented and actively monitored. Reports suggest outpatient antibiotic use of antibiotics is high and that non-prescription access and self-medication are very common. Antibiotic susceptibility studies in Russia include PeHASus, a multicentre epidemiological study focusing on susceptibilities of community-acquired respiratory pathogens and international studies such as Survey of Antibiotic Resistance (SOAR), Antimicrobial Testing Leadership and Surveillance (ATLAS) and SENTRY Antimicrobial Surveillance Program. International guidelines are used to support the development of local guidelines in Russia, and for the common CA-RTIs Russian clinicians use of several country-specific local antibiotic prescribing guidelines. A standardized inclusive approach in developing local guidelines, using up-to-date surveillance data of isolates from community-acquired infections in Russia, could make guideline use more locally relevant for clinicians. This would pave the way for a higher level of appropriate antibiotic prescribing and improved adherence. This would, in turn, potentially limit AMR development and improve patient outcomes.